Climatological comparison of polar mesosphere summer echoes over the Arctic and Antarctica at 69° - R. Latteck; D. J. Murphy (Annales Geophysicae, 2024)
Polar mesosphere summer echoes (PMSE) have been observed for more than 30 years with 50 MHz VHF radars at various locations in the Northern Hemisphere. Continuous observation of PMSE is conducted on the northern Norwegian island of Andøya (69.3° N) using the ALWIN radar (1999–2008) and MAARSY (since 2010). The same kind of PMSE measurements began in 2004 in the Southern Hemisphere with the Australian Antarctic Division's VHF radar at Davis Station in Antarctica (68.6° S), which is at an opposite latitude to Andøya. Since the radars at both sites are calibrated, the received echo strength of PMSE from more than 1 decade of mesospheric observations on both hemispheres could be converted to absolute signal power, allowing for direct comparison of the measurements. Comparison of PMSE observations obtained at both radar sites during a period of 23 boreal summers (Andøya) and 15 austral summers (Davis) shows that their PMSE signal strengths are of the same order of magnitude, but significantly fewer PMSE are observed in the Southern Hemisphere than in the Northern Hemisphere. Compared to Andøya, the PMSE season over Davis starts about 7 d later on average and ends 9 d earlier, making it 16 d shorter. PMSE over Davis occur less frequently but with greater variability in seasonal, diurnal, and altitudinal occurrence. For example, PMSE over Davis reach maximum altitudes about 1.5 km higher than those over Andøya.